Cutting Time and Regrowth Age Affect the Quality of Elephant Grass Silage - Silveira, Tâmara Chagas da; Ribeiro, Karina Guimarães; Roseira, João Paulo Santos; Alves, Wagner Sousa; Anjos, Albert Jose dos; Coutinho, Danielle Nascimento; Freitas, Cássia Aparecida Soares; Pereira, Odilon Gomes (Journal of Agricultural Studies, 2021)
The objective of this study was to evaluate the effects of regrowth age (RA) and cutting time (CT) of elephant grass (Cenchrus purpureus cv. Cameroon) on the fermentation profile, microorganism population, and nutritive value of the silage in two simultaneous trials at different sites. A 2 × 2 factorial scheme with two CTs (08:00 and 14:00) and two RAs (8 and 16 weeks) at ensilage was used in a completely randomized design, with four replicates in each trial, totaling 16 experimental units per trial. Results showed that ammonia nitrogen to total nitrogen content (N-NH3/TN) ranged from 71.8 (14:00; 16 weeks) to 137.0 g kg -1 (14:00; 8 weeks). Elephant grass silage harvested at 14:00 at 8 weeks had the lowest pH (3.53) and highest lactic acid content (39.7 g kg-1 dry matter). The in vitro dry matter digestibility (IVDMD) was higher (P < 0.05) in the silage of plants harvested at 8 weeks than in the silage harvested at 16 weeks (59.9 vs. 46.8%, respectively). In trial 2, elephant grass silage harvested at 14:00 had lower pH and acetic acid content. The IVDMD was higher in elephant grass silage harvested at 14:00, with values of 65.3% and 56.2% at 8 and 16 weeks, respectively. We recommend elephant grass harvested at 8 weeks of regrowth and cut at 14:00 to produce silage with better nutritive value and fermentative profile.